2007
DOI: 10.1097/ta.0b013e318060d2b9
|View full text |Cite
|
Sign up to set email alerts
|

Odontoid Fractures in the Elderly: Dorsal C1/C2 Fusion is Superior to Halo-Vest Immobilization

Abstract: Posterior stabilization of unstable odontoid fractures with transarticular screws and modified Gallie fusion in old patients can be performed safely, with good clinical results and few complications. However, mortality remains high, but is lower than reported after halo-vest immobilization alone. Dorsal C1/C2 Fusion is superior to halo-vest immobilization in terms of nonunion rate and mortality. Thus, it might be the treatment of choice in this high-risk patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
75
2
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(81 citation statements)
references
References 29 publications
2
75
2
2
Order By: Relevance
“…Although some authors advocate external immobilisation as the treatment of choice for type II OF in an elderly population [7,11,20], high fusion rate and best clinical outcome are obtained by surgical treatment [5,8,13,14,[17][18][19]. Bone fusion rate in our series (44%) was lower than bone fusion rate described in the literature [17,19] which ranged from 80 to 100%.…”
Section: Discussioncontrasting
confidence: 58%
See 3 more Smart Citations
“…Although some authors advocate external immobilisation as the treatment of choice for type II OF in an elderly population [7,11,20], high fusion rate and best clinical outcome are obtained by surgical treatment [5,8,13,14,[17][18][19]. Bone fusion rate in our series (44%) was lower than bone fusion rate described in the literature [17,19] which ranged from 80 to 100%.…”
Section: Discussioncontrasting
confidence: 58%
“…In this study, the morbidity rate was 62% without distinction between surgical procedures. The other studies did not distinguish octogenarians from other elderly patients [3,5,7,8,11,13,15,18,24,25]. We specifically studied type IIB OF because among all types of OF they are considered as the most unstable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite a high [22% (n = 6)] mortality rate in 27 elderly patients with type II odontoid fractures Frangen et al [17] found the results of dorsal C1/C2 fusion superior to halo-vest immobilization.…”
Section: Discussionmentioning
confidence: 99%